Radiological and clinical evaluation of cockayne syndrome: A case report - Kumar, Amit; Suman, Sanjay K; Prasad, Umakant (Indian Journal of Case Reports, 2017)
Cockayne syndrome (CS) is a rare autosomal recessive disorder characterized by premature ageing (progeria), facial anomalies, cachectic dwarfism, mental retardation, cutaneous photosensitivity, and retinopathy, loss of adipose tissue and muscle, and neurological abnormality which are associated with the changes in the brain parenchyma. The findings of computed tomography scan and especially magnetic resonance imaging of the brain support the clinical diagnosis of CS. There is no permanent cure of this condition and death usually occurs in the 2nd or 3rd decade due to functional disability and multiple infections.